Characterization of the tailing paste for using as a filling in mining working - Romero Baylón, Alfonso (2010)
The present paper makes reference to the study of the technical parameters of the tailing from Ticapampa and its application for the filling in paste. For this case, it has been considered as a typical case, the tailing from Ticapampa, which it is the most representative and important because its several composition. As it is well know, the paste is a mixing of water with solids of high density which contains a lot of fine particles with a lower water content, which is controlled by the Abrahams Cone. The main purpose of this study is based in the establishment of the technical parameters of the properties of the filling paste derived from the tailing which is used as a material of hydraulic filling in the underground mining works such as the main galleries, the mining shafts and chopping blocks and others that require support and protection to the geologic environment surrounded of the future sinking and fails caused for these mining works.